2001
DOI: 10.2166/wqrj.2001.001
|View full text |Cite
|
Sign up to set email alerts
|

A Computer Simulation of Water Quality Change Due to Dredging of Heavy Metals Contaminated Sediments in the Old Harbour of Montreal

Abstract: Aquatic sediments accumulate heavy metals that are discharged into the environment. This study investigates possible water quality changes due to release of heavy metals such as Cd, Ni, Zn and Pb into the water column during dredging of anoxic sediments in the Old Harbour of Montreal. An environmental impact assessment of the sediment removal requires estimating the speciation of heavy metals in the water column with and without the solid phase. Chemical equilibria in the St. Lawrence River water are calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 78 publications
3
3
0
Order By: Relevance
“…Similar to the findings of this study, many investigations (Calmano et al, 1993; Degtiareva and Elektorowicz, 2001; Dubrovsky et al, 1985; Lors et al, 2004) have shown a distinct pH drop after exposing the anoxic sediments to oxygenated overlying waters, and it was suggested that the oxidation of AVS and other iron sulfide minerals was the primary source of the increased acidity, according to the following reactions: 2FeS, solid + 9/2normalO2 + 5normalH2O 2Fe(OH)3, solid + 2SO42 + 4normalH+ FeS2, solid + 15/4normalO2 + 5/2normalH2O 2FeOOH, solid + 2SO42 + 4normalH+As shown in Eq. [1] and [2], 1 mol of AVS can produce 2 mol of H + , whereas 1 mol of pyrite can produce 4 mol of hydrogen ions.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Similar to the findings of this study, many investigations (Calmano et al, 1993; Degtiareva and Elektorowicz, 2001; Dubrovsky et al, 1985; Lors et al, 2004) have shown a distinct pH drop after exposing the anoxic sediments to oxygenated overlying waters, and it was suggested that the oxidation of AVS and other iron sulfide minerals was the primary source of the increased acidity, according to the following reactions: 2FeS, solid + 9/2normalO2 + 5normalH2O 2Fe(OH)3, solid + 2SO42 + 4normalH+ FeS2, solid + 15/4normalO2 + 5/2normalH2O 2FeOOH, solid + 2SO42 + 4normalH+As shown in Eq. [1] and [2], 1 mol of AVS can produce 2 mol of H + , whereas 1 mol of pyrite can produce 4 mol of hydrogen ions.…”
Section: Resultssupporting
confidence: 92%
“…In agreement with our observations, Degtiareva and Elektorowicz (2001) and Lors et al (2004) demonstrated that the fate of toxic metals during resuspension depended on the calcium content in the sediment. In contrast, Calmano et al (1994) reported a continuous increase in dissolved Cu, Cd, and Zn concentrations after sediment resuspension at pH 7.5.…”
Section: Resuspension In Well Buff Ered Systemssupporting
confidence: 92%
See 3 more Smart Citations